FORCED CONVECTION IN DUCTS WITH PERMEABLE WALLS - Alexandrino, C. H.; Martins-Costa, M. L. (Revista de Engenharia Térmica, 2003)
A mixture theory model is employed in a local description of the energy transfer in a duct with permeable wall which is simulated by considering two distinct flow regions, one consisting of a Newtonian incompressible fluid and the other represented by a binary (solid-fluid) mixture. Compatibility conditions at the interface (pure fluid-mixture) for momentum and energy transfer are considered. The simulations are carried out by using a finite difference approach with an upwind strategy for the convective term discretization.